Strategi Pembelajaran Kontekstual - Shoif Auliyauddin; Usman U; M. Shabir U (Madani: Jurnal Ilmiah Multidisiplin, 2025)
A deep understanding of religion is needed. Religious studies do not only discuss the relationship between humans and Allah (?abl min All?h), but also the relationship with oneself, fellow citizens, fellow humans (?abl min al-n?s) and the universe. Therefore, a learning strategy is needed that is not only in the form of lectures, but requires a more interactive strategy. Therefore, in this paper the author will try to discuss one of the strategies, namely the contextual learning strategy that can be applied in the PAI learning process, so that learning objectives can be achieved. In this study, the author uses a qualitative descriptive method with primary data from library data. The results of the study show that the characteristics of contextual learning according to Muslich are as follows: a) Learning is carried out in an authentic context, b) Learning provides opportunities for students to work on meaningful tasks, c) Learning is carried out by providing meaningful experiences to students, d) Learning is carried out through group work, discussion, correcting each other between friends, e) Learning provides opportunities to create a sense of togetherness, f) Learning is carried out actively, creatively, productively, and prioritizes cooperation, g) Learning is carried out in a pleasant situation The advantages of contextual learning strategies include more meaningful and real learning, more productive learning and being able to foster reinforcement of concepts to students. The disadvantages are: If the teacher cannot control the class, it can create a less conducive class situation.